2022
DOI: 10.3390/app12126028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Parameters on Tensile Strength of FDM Printed Carbon Fiber Reinforced Polyamide Parts

Abstract: Reinforcing the polymer with nanoparticles and fibers improves the mechanical, thermal and electrical properties. Owing to this, the functional parts produced by the FDM process of such materials can be used in industrial applications. However, optimal parameters’ selection is crucial to produce parts with optimal properties, such as mechanical strength. This paper focuses on the analysis of influential process parameters on the tensile strength of FDM printed parts. Two statistical methods, RSM and ANN, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…PCR-TOPSIS was used to find the optimal process parameters condition [37]. Muhamedagic et al [95] investigated the effect of layer height, print speed, raster angle, and wall thickness on the tensile strength of the specimen built using short carbon fiber reinforced polymide composite. The reduced cubic model was established using RSM and the correlation between selected process parameters and performance parameter was anlyzed by ANOVA.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR-TOPSIS was used to find the optimal process parameters condition [37]. Muhamedagic et al [95] investigated the effect of layer height, print speed, raster angle, and wall thickness on the tensile strength of the specimen built using short carbon fiber reinforced polymide composite. The reduced cubic model was established using RSM and the correlation between selected process parameters and performance parameter was anlyzed by ANOVA.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The reduced cubic model was established using RSM and the correlation between selected process parameters and performance parameter was anlyzed by ANOVA. The layer thickness and raster angle were found most influential factors for tensile strength [95]. Ahmed et al [2] identified the influence of layer thickness, build orientation, infill density, and print speed on tensile strength, Young's modulus, and flexural strength.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The X and Y axes are considered parallel to the build platform, whereas the Z axis is along the part build direction. 207 Layer thickness refers to the thickness of the sedimentary layer.…”
Section: Optimization Of Process Parametersmentioning
confidence: 99%
“…206 Similarly, the optimization of process parameters can also be done using ANN artificial neural networks (Figure 8G). 207…”
Section: Optimization Of Process Parametersmentioning
confidence: 99%
See 1 more Smart Citation